Memory T Cells - Zanetti, Maurizio; Schoenberger, Stephen P. (Advances in Experimental Medicine and Biology,, 2010)
Immunological memory has fascinated microbiologists and immunologists for decades as one of the new frontiers to conquer to better understand the response to pathogens, cancer and vaccination. Over the past decade, attention has turned to the intrinsic properties of the memory T cells themselves, as it has become clear that the eradication of both infected cells and tumors requires T cells. This book is an attempt to capture the wave of discoveries associated with these recent studies. Its chapters represent a wide collection of topics related to memory T cells by laboratories that have invested their skills and knowledge to understand the biology and the principles upon which memory T cells are generated, maintained and expanded upon re-encounter with antigen. Ultimately, these studies are all aimed at a better understanding of the function of memory T cells in protection against disease.